614 ChatGPT: "To be or not to be" ... in academic research. The human mind's analytical rigor and capacity to discriminate between AI bots' truths and hallucinations (Balneo and PRM Research Journal, 2024)
ChatGPT can generate increasingly realistic language, but the correctness and integrity of implementing these models in scientific papers remain unknown.Recently published literature emphasized the „three faces of the coin” of ChatGPT: the negative impact on academic writing, limitations in analyzing and conducting extensive searches of references across multiple databases, and the superiority of the human mind.Method.  Starting from previous papers published in our clinic, the authors repeatedly challenged the ChatGTP chatbot to conduct extensive searches for references across multiple databases at different time intervals.